SOME ISSUES OF DISMISSAL OF CRIMINAL CASES IN CONNECTION WITH THE EXPIRATION OF THE LIMITATION PERIOD FOR CRIMINAL RESPONSIBILITY - Maxmudov Sunnat (Scholar Express Journals, 2023)
In this article, at the stage of implementation of the judicial and legal reform, the institution of exemption from criminal liability due to the expiration of the statute of limitations for bringing to the responsibility based on criminal and criminal procedure legislation, the procedure, conditions for terminating a criminal case on this basis and the features of its application are studied. At the same time, this article provides evidence-based opinions and comments on some of the problems that may arise when a criminal case is terminated due to the expiration of the statute of limitations for prosecution and their solution. Based on the results of the analysis, relevant proposals and recommendations were developed to improve the procedure for terminating a criminal case due to the expiration of the statute of limitations as a basis for terminating a criminal case without resolving the issue of guilt.
Keywords: guilty; responsibility; release from liability; termination of a criminal case